2001
DOI: 10.1046/j.1038-5282.2001.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural Training and the State of Rural Health Services: Effect of Rural Background on the Perception and Attitude of First‐year Medical Students at the University of Melbourne

Abstract: The aim of this project is to investigate the relationship between medical students' background and their perception of the state of rural health services; willingness to undertake internship training or work as a doctor in a rural hospital; expected benefits and disadvantages of training or working as a doctor in a rural hospital; and factors interfering with acceptance of a job as a doctor in rural areas. A questionnaire-based survey was distributed to 100 first-year medical students attending the Faculty of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 13 publications
6
42
1
Order By: Relevance
“…2,3 Against a general background of negative urban attitudes to rural practice, 4 rural placement programs effectively promote positive attitudes and career plans for students of all health disciplines. [5][6][7][8][9][10][11] Longitudinal studies of medical students that have explicitly linked rural placements with students' actual career choice have had inconsistent results. 2,[12][13][14][15][16][17] These studies are complicated by the fact that most medical students spend two to six years post graduation in urban hospitals to gain vocational experiences and qualifications.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Against a general background of negative urban attitudes to rural practice, 4 rural placement programs effectively promote positive attitudes and career plans for students of all health disciplines. [5][6][7][8][9][10][11] Longitudinal studies of medical students that have explicitly linked rural placements with students' actual career choice have had inconsistent results. 2,[12][13][14][15][16][17] These studies are complicated by the fact that most medical students spend two to six years post graduation in urban hospitals to gain vocational experiences and qualifications.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the highly praised role of rural practices is also found by other studies, in which students agreed that the delivery of health care in rural areas is important [12]. A positive attitude towards health care services in rural areas was presented in a study by Azer et al [13].…”
Section: Role Of Rural Practices In the Medical Systemmentioning
confidence: 58%
“…The Australian study by Azer et al identified similar advantages of a rural environment, e.g. greater appreciation by patients, a friendly environment, less pressure and stress [13].…”
Section: Conditions Under Which Students Would Work In Rural Practicementioning
confidence: 88%
See 1 more Smart Citation
“…Curriculum and rurally based clinical opportunities have been found to positively influence perceptions of rural practice [19, 20]. Current JCU graduate outcomes indicate rural experiences have a positive impact on both intent and reality of practising in rural locations.…”
Section: Discussionmentioning
confidence: 99%